Relevance of Nanomedicine to Veterinary Science: An Insight - Gerish E1*, Mansour L2; AlKateb A3 (AlQalam Journal of Medical and Applied Sciences, 2017)
Nanotechnology is no more being a concept or theory of the new world, but has turned into a new enabling technology over the years, with tremendous potential to revolutionize agriculture and livestock. Nanotechnology has the potential to solve many more puzzles related to animal health, production, reproduction, good hygienic practices during rearing and maintaining of food animals, the possible applications of the technology is almost incredible in relation to livestock. It can provide new tools for molecular and cellular biology, biotechnology, veterinary physiology, animal genetics, reproduction etc. which will allow researchers to handle biological materials such as DNA, proteins or cells in minute quantities usually nano-liters or pico-liters. Nanotechnology tools like microfluidics, nanomaterials, bioanalytical nanosensors, etc. Existing research has clearly demonstrated the feasibility of introducing nanoshells and nanotubes into animal systems to seek out and destroy targeted cells. Nanoparticles smaller than one micron have been used to deliver drugs and genes into cells. Thus in this contribution will provide a glimpse of the probable future of nanomedicine in veterinary science and keep veterinarians abreast of the emerging technology. It is reasonable to presume over the next couple of decades that nanobiotechnology industries and unique developments will revolutionise animal health and medicine. In spite of all benefits and opportunities which use of nanotechnology offers, it is still in the early stages of its development and not applied throughout the world. Also, there are little concerns about impact of nanoparticles on animal health and environment.